Impact of mastectomy and chemotherapy on haematological parameters in breast cancer patients at Mostaganem University Hospital oncology center. - Kupe, Francoise Taboka; Mwemba, Rachael Mambori (My University, 2024)
Breast cancer ranks among the most prevalent cancers affecting women. Mastectomy and chemotherapy are crucial elements of its treatment, markedly affecting patients' haematological parameters and often resulting in anaemia, leukopenia, and thrombocytopenia. This study aims to examine the alterations in haematological parameters before and after these treatment methods in breast cancer patients in Mostaganem, Algeria. The study included 72 patients from 2019 to 2024, with 70 receiving chemotherapy and 28 undergoing mastectomy. Medical records from the Mostaganem University Hospital oncology centre were utilised, focusing on patients who had undergone six cycles of chemotherapy and those who had only undergone mastectomy. Data on erythrocytes and their indices, leukocytes, platelets, haemoglobin, and haematocrit levels before and after chemotherapy and mastectomy were analysed. All patients exhibited anaemia following chemotherapy, evidenced by low erythrocyte counts (3.99 μL uniquely in the 40-49 age group), haematocrit (mean value 34.84%), and haemoglobin (mean value 11.52 g/dL). Neutrophil, leukocyte, and thrombocyte levels varied depending on age and chemotherapy cycles. Similarly, all patients were anaemic both before and after surgical resection, with consistently low erythrocyte counts (mean value 4 μL), haematocrit (mean value 35.40%), and haemoglobin levels. Neutrophil levels remained within the normal range, while thrombocyte and leukocyte levels showed age-related variations. Chemotherapy and mastectomy for breast cancer can lead to decreased haematological parameters and anaemia in patients. However, subsequent clinical monitoring, the use of haematopoiesis boosters, and maintaining a well-balanced nutrition regimen can mitigate these adverse effects.
Keywords: Breast cancer; mastectomy; chemotherapy; haematological parameters